Crashworthiness optimisation of A-pillar in passenger car in rear-end collision with truck. Issue 6 (1st November 2016) - Yang, Na; Cao, Pengfei; Liu, Tao; Wang, Jianfeng; Wang, Dafang
ABSTRACT: Rear-end collisions between cars and trucks are of great concern to society because of their high casualty rate. Improving the safety of passengers during these collisions is a significant issue. This paper aims to optimise the crashworthiness of the A-pillar area of a car according to the collision form based on the finite-element model of the car–truck rear-end collision. Through the optimisation process, the value and speed of the intrusion into the A-pillar were selected as the evaluation assessment indicators, and the optimisation design was conducted from two viewpoints: the material selection and stiffness match. As a result of the optimisation, the maximum intrusion of the A-pillar of the car was reduced by 33.19%, and the intrusion speed was reduced by 46.98% without increasing the body mass of the car. These results indicate that the crashworthiness of the car was improved effectively; thus, the occupant casualty risk was reduced. They suggest a feasible path for the crashworthiness improvements of automobiles for rear-end collisions.